Recent developments in particle symmetries : 1965 International School of Physics 'Ettore Majorana', a CERN-MPI-NATO Advanced Study Institute - Zichichi, Antonino (Academic Press, 1966)
Recent Developments in Particle Symmetries focuses on the advancements of processes, technologies, reactions, transformations, and approaches in particle symmetries. The selection first offers information on higher symmetries and deviations from unitary symmetry, including S matrix and perturbation theory and bootstrap theory of octet enhancement. The text then ponders on broken symmetries and sum rules and difficulties of relativistic U(6). Discussions focus on covariant models, unitary, Coleman's theorems, saturation of commutation relations and particle multiplets, and exact internal symme.